2013
DOI: 10.1017/s0967199413000555
|View full text |Cite
|
Sign up to set email alerts
|

Oviductal and endometrial mRNA expression of implantation candidate biomarkers during early pregnancy in rabbit

Abstract: SummaryPrenatal losses are a complex problem. Pregnancy requires orchestrated communication between the embryo and the uterus that includes secretions from the embryo to signal pregnancy recognition and secretion and remodelling from the uterine epithelium. Most of these losses are characterized by asynchronization between embryo and uterus. To better understand possible causes, an analysis was conducted of gene expression of a set of transcripts related to maternal recognition and establishment of rabbit preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 81 publications
(96 reference statements)
1
1
0
3
Order By: Relevance
“…IGF1 plays crucial roles in the regulation of sexual development and reproduction in mammals [ 58 ]. Numerous studies have shown that members of the integrin family are highly expressed in the gonadal axis of female animals and play an important role in embryonic attachment [ 59 , 60 , 61 ], and the present study showed that the ITGAM , ITGAV , ITGA1 , ITGA5 , ITGB1, and ITGB2 integrin families are highly expressed in the treatment group, which suggests that integrins play an important role in the modulation of reproduction in does. KRAS plays an important role in regulating the implantation process in mouse embryos [ 62 ].…”
Section: Discussionsupporting
confidence: 73%
“…IGF1 plays crucial roles in the regulation of sexual development and reproduction in mammals [ 58 ]. Numerous studies have shown that members of the integrin family are highly expressed in the gonadal axis of female animals and play an important role in embryonic attachment [ 59 , 60 , 61 ], and the present study showed that the ITGAM , ITGAV , ITGA1 , ITGA5 , ITGB1, and ITGB2 integrin families are highly expressed in the treatment group, which suggests that integrins play an important role in the modulation of reproduction in does. KRAS plays an important role in regulating the implantation process in mouse embryos [ 62 ].…”
Section: Discussionsupporting
confidence: 73%
“…Tavşanlarda düzenli bir östrus döngüsü yoktur [12]. Ovulasyon çiftleşmeye, benzer manipülasyonlara ya da hormon kullanımına bağlıdır [13] [16]. Bu esnada vasküler endotelyal büyüme faktörü salınarak mikrovasküler endotelyal hücre proliferasyonu, embriyogenez, korpus luteum gelişimi ve implantasyonda neovaskülarizasyonla ilişkili hücre göçünü artırır.…”
Section: Tavşanlarda Gebelik Fizyolojisiunclassified
“…Bu aşamadan sonra serum östrojen seviyesi düşmeye başlayarak [15] bazal seviyede bulunan P4 konsantrasyonu (<2 ng/mL) [13] yükselmeye başlar ve gebelik süresince yüksek seyreder. Gebeliğin ilk günlerinde uterus epitelyumunda trofoblast odakcıkları olarak bilinen blastosist bağlanma noktalarının oluşması, histotrof uterus sekresyonundan uteroglobin (SCGB1A1) salınımı artmaya başlaması gebelik için uygun ortamı hazırlar [16]. Bu esnada vasküler endotelyal büyüme faktörü salınarak mikrovasküler endotelyal hücre proliferasyonu, embriyogenez, korpus luteum gelişimi ve implantasyonda neovaskülarizasyonla ilişkili hücre göçünü artırır.…”
Section: Tavşanlarda Gebelik Fizyolojisiunclassified
See 1 more Smart Citation
“…The product of this gene is oviductal glycoprotein 1 (OVGP1), which is one of the major components of oviductal fluid (Yu et al, 2019 ). This fluid provides the ideal environment, including temperature, pH, and oxygen tension, and also controls early pregnancy (Killian, 2004 ; Saeed et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%